8 The value of serial echocardiography in asymptomatic patients at risk of heart failure with incident of BNP >50 pg/ml. (7th October 2015) - Abusalma, Y; O'Connell, E; Kenny, C; McDonald, K
Abstract : Background: Controversy exists as to the value of serial echocardiography for monitoring asymptomatic patients at risk for cardiovascular events. We aimed to identify whether new structural cardiac abnormalities identified by serial transthoracic echocardiography, provide incremental prognostic information above conventional risk profiling and natriuretic peptic measurement in a cohort at risk for cardiovascular events. Methods: Patients from the STOP-HF cohort with a BNP of ≥50 pg/mL at any point during screening who underwent transthoracic echocardiography on at least 2 occasions 18–36 months apart were included. All patients were aged >40 y had at least one conventional cardiovascular risk factor (hypertension, hypercholesterolaemia, diabetes, obesity, vascular disease or arrhythmia) Patients with baseline left ventricular systolic dysfunction (LVSD) were excluded. The following changes from baseline to follow-up echo were considered significant: a) EF drop of ≥ 10%, b) LAVI rise of ≥ 3.5 mL/m 2, c) newly diagnosed RWMA, d) newly diagnosed LVH, e) newly diagnosed moderate/severe valvular (MV/AV/AT) regurgitation or stenosis. Missing data were assumed to mean no change. Major Adverse Cardiovascular Events (MACE) were defined as any emergency admission for HF, MI, Arrhythmia, Stroke/TIA or PE/DVT, and any admission for ADHF or admission otherwise classified as cardiovascular emergency. Events were identified from patients GP records and from the chronic cardiovascular diseases unit database. The primary endpoint was one or more MACE occurring after the date of a patients follow-up echo. Statistical Analysis was performed using generalised linear modelling with a binomial outcome. P values are calculated using the z-score derived from the model coefficient estimate and standard error. Results: Complete echo information was available for 197 patients. Of these, 77 showed a significant echo change. MACE prevalence was 14 (11.7%) in patients with no echo change and 18 (23.4%) in those showing significant echo change. Patients with a significant echo change were on average more than twice as likely to have at least one MACE after their follow-up echo (OR = 2.31 [1.07, 4.98], p = 0.033). Controlling for the presence of any inter-echo MACE and baseline BNP did not change this relationship between echo change and MACE (OR = 2.43 [1.11, 5.32], p = 0.026). Conclusion: Asymptomatic, at risk patients who demonstrate a structural change at serial echocardiography are at higher risk for significant cardiovascular events. Transthoracic echocardiography provides incremental prognostic information above clinical risk profiling and natriuretic peptides for patients at risk for cardiovascular events.